Targeting Mitochondrial Dysfunction in Acute Organophosphate Toxicity: A Preliminary Evaluation of Cyclosporine A - David H. Jang; Jarelis Cabrera; Jonathan Starr; Abigail Insana; Angela N. Viaene; John C. Greenwood; Frances S. Shofer; Johannes K. Ehinger; Shih-Han Kao; Todd J. Kilbaugh (Journal of Medical Toxicology, 2026)
Background Organophosphate (OP) compounds are widely used agricultural chemicals that pose significant public health and chemical threat concerns due to their neurotoxic effects. Although OP toxicity has classically been attributed to acetylcholinesterase inhibition and cholinergic crisis, emerging evidence suggests mitochondrial dysfunction may represent an additional and clinically relevant mechanism of injury. Experimental OP exposure has been associated with impaired electron transport chain activity, reduced ATP production, increased oxidative stress, and disruption of mitochondrial membrane integrity. However, there are currently no established mitochondrial-targeted therapies for OP poisoning. Diisopropyl fluorophosphate (DFP), a well-established OP surrogate, reproduces several neurologic and mitochondrial features of nerve agent exposure. Cyclosporine A (CsA), an inhibitor of the mitochondrial permeability transition pore (mPTP), may represent a potential mitochondrial-targeted intervention. Methods This preliminary translational study employed both in vitro and in vivo models to evaluate mitochondrial respiratory dysfunction following acute DFP exposure and to explore the feasibility of mitochondrial-targeted treatment paradigms using CsA. Human donor-derived peripheral blood mononuclear cells (PBMCs) were used for DFP and CsA dose-finding and mitochondrial respiratory characterization using high-resolution respirometry (Oroboros O2k) with standardized substrate–uncoupler–inhibitor titration (SUIT) protocols. In parallel, a non-survivor Sprague–Dawley rat model of acute DFP exposure was developed incorporating invasive hemodynamic monitoring, controlled ventilation, venous blood gas analysis, and CsA treatment paradigms administered either following DFP exposure or as pretreatment prior to exposure. Brain cortical homogenates were prepared for ex vivo respiratory assessment. Results Preliminary findings demonstrated that DFP exposure was descriptively associated with impaired mitochondrial respiration across multiple oxidative phosphorylation (OXPHOS)- and electron transport system (ETS)-linked respiratory states in both PBMC and rodent models. DFP exposure was additionally associated with physiologic and metabolic derangements, including acidosis and elevated lactate concentrations. Post-DFP CsA administration was associated with partial preservation of mitochondrial respiration across several respiratory states, while the Pre-DFP CsA group demonstrated respiratory profiles more closely approximating control values in select OXPHOS- and ETS-linked states, accompanied by relatively preserved physiologic and metabolic parameters. Conclusions These preliminary findings support the feasibility of integrating mitochondrial respiratory phenotyping into translational models of acute OP toxicity and further support investigation of mitochondrial-targeted strategies in OP-associated mitochondrial dysfunction. The observed respiratory and physiologic trends associated with CsA exposure, particularly in the pretreatment paradigm, provide an exploratory foundation for future preclinical studies evaluating mitochondrial-directed countermeasures in OP poisoning.